EFFECTIVE CONTROL OF SYMPTOMS AT PATIENTS WITH ALLERGIC RHINITIS - V. M. Svistushkin; E. V. Sinkov (Медицинский совет, 2017)
According to the forecast of WHO, by 2020  every second child will have allergic diseases. Allergic rhinitis occupies one of the leading positions in structure of allergic diseases of the person. The special attention of scientific and practical health care to this question is caused by the whole range of both medical, and social aspects. Treatment of allergic rhinitis demands the reasonable and integrated approach considering pathogenesis of a disease.